Basaloid carcinoma of the anal canal - Pang, Lillian S. C. (1967)
The pathology and results of treatment of 36 cases of basaloid carcinomas of the anal canal are described. This variant of squamous cell carcinoma of the anal region arises from the entodermal-ectodermal junctional zone of the anal canal at or above the dentate line. Basaloid carcinomas have histological characteristics which resemble basal cell carcinoma of the skin, in particular the presence of palisading of the nuclei at the periphery of the clumps of tumour cells, but are potentially metastasizing tumours. They have been subdivided into three grades of malignancy, namely, well-differentiated, moderately differentiated, and anaplastic basaloid carcinoma. It has been shown that cases of well-differentiated and moderately differentiated basaloids have a good prognosis even when lymph node metastasis has already taken place. Those of anaplastic basaloid carcinoma have a very poor prognosis even in the absence of lymphatic metastases.